Educating Future Teachers: Innovative Perspectives in Professional Experience (Springer Singapore, 2018)
This book describes, problematises and theorises professional practice research in a range of Australian settings to provide evidence of robust, wide-ranging and contemporary approaches to professional experience in initial teacher education. It presents the latest research and evidence from those currently involved in innovative programmes designed to provide alternatives to meet local challenges during professional experience in teacher education. As the professional experience process is framed quite differently across Australian teacher education programmes, these cross-institutional accounts of collaboration, innovation and success make a major contribution to the field, both nationally and internationally. The book was developed from a research workshop funded by an Australian Association for Research in Education grant and organised by the Teacher Education Research and Innovation Special Interest Group.